Investigation of mechanical properties of Al6061-T6 alloy by EAFSW with straight and reverse polarity of direct current. (2021) - Chowdhury, Ivy Das; Sengupta, Kaushik; Singh, Dilip K.; Daskarmakar, Abhijit; Roy, Swapna; Ghosal, Sujit; Mondal, A.K.
Abstract: Electric Resistance Friction Stir welding has been invented as one of the hybrid technologies and produces less tear and wear of the tool with least defects at the produced joint. The study focuses on the Electrical Assisted friction stir welding (EAFSW) of Al6061 alloy. In this experiment an attempt has been made and evaluated to derive the optimum mechanical properties by adjusting the rotational speed, welding speed and current in the range of 500–900 rpm, 10–25 mm/min and 25–75 amps, both in reverse polarity and straight polarity. In the present study, mechanical properties of welded joints using conventional FSW have compared with that of Electrically Assisted Friction Stir Welding (EAFSW) with two different approaches. The rotation speed, travel speed and current were the primary welding parameters which considered. The Rockwell hardness, ultimate tensile strength and weld efficiency of the welded joints were found out for the above-mentioned cases and a comparative study of the mechanical properties have been done. It has been observed that better weld efficiency and hardness has been obtained in Direct Current Reverse Polarity EAFSW. Straight polarity to EAFSW process had been found to decrease the weld efficiency of the joint, whereas, the reverse polarity DC has been proved to be adding weld efficiency in the joint for Al6061-T6 Al alloy.